The single-stranded DNA end binding site of p53 coincides with the C-terminal regulatory region. - Selivanova, G (1996)
p53 is a transcription factor that binds double-stranded (ds) DNA in a sequence-specific manner. In addition, p53 can bind the ends of single-stranded (ss) DNA. We previously demonstrated that ssDNA oligonucleotides interact with the C-terminal domain of p53 and stimulate binding to internal segments of long ssDNA by the p53 core domain. Here we show that the p53 C-terminal domain can recognize staggered ss ends of dsDNA. We have mapped the binding site for ssDNA ends to residues 361-382 in human p53 using a p53 deletion mutant (p53-delta 30) lacking the 30 C-terminal amino acid residues and a series of 22mer peptides. The binding site for DNA ends coincides with a region previously implicated in regulation of sequence-specific DNA binding by the core domain. The interaction of the C-terminal regulatory domain with the ends of ssDNA or with the protruding ends of dsDNA stimulates both sequence-specific and non-specific DNA binding via the core domain. Electron microscopy demonstrated the simultaneous binding of p53 to dsDNA and a ssDNA end. These results suggest a model in which interaction of the p53 C-terminal tail with DNA ends generated after DNA damage causes activation of sequence-specific p53 DNA binding in vivo and may thus provide a molecular link between DNA damage and p53-mediated growth arrest and apoptosis.